Effects of time-of-day resistance training on muscle strength, hormonal adaptations, and sleep quality during Ramadan fasting - Triki, Raoua; Ben Abderrahman, Abderraouf; Salhi, Iyed; Rhibi, Fatma; Saeidi, Ayoub; Almaqhawi, Abdullah; Hackney, Anthony C.; Laher, Ismail; Granacher, Urs; Zouhal, Hassane (Frontiers in Nutrition, 2024)
Objectives We investigated the timing of resistance training (RT) during Ramadan fasting (RF) on muscle strength, hormonal adaptations, and sleep quality. Methods Forty healthy and physically active male Muslims (age = 25.7 ± 5.6 years, body mass = 85.1 ± 17.5 kg, height = 175 ± 9 cm, BMI = 28.3 ± 5.7 kg/m2) were enrolled in this study and 37 completed pre and post-tests. Subjects were randomly allocated into two experimental groups. Group 1 (FAST, n = 20) completed an 8-week whole-body RT in the late afternoon (between 16 h and 18 h) while fasting. Group 2 (FED, n = 20) completed the similar RT protocol compared with FAST at night (between 20 h and 22 h). The following parameters were analyzed at various time-points: 2 weeks before the start of RF (T0), on the 15th day of Ramadan (T1), on the 29th day of Ramadan (T2), and 21 days after the last day of RF (T3) where both groups were in a fed state. One-repetition maximum tests (1-RM) were conducted for the squats (1-RMSQ), the deadlift (1-RMDL) and the bench press (1-RMBP). Sleep quality was assessed using the full Pittsburgh Sleep Quality Index (PSQI). Blood samples were taken to determine cortisol, testosterone and IGF-1 levels. Additionally, acute hormonal responses were evaluated before (BF), immediately after (AF), and 30 min after a RT session (AF-30 min) at T0, T1, T2, and T3. Results Significant group-by-time interactions were identified for 1-RMSQ (p = 0.001; effect size [ES] = 0.43) and 1-RMDL (p = 0.001; ES = 0.36). Post-hoc tests indicated significant 1-RMSQ (p = 0.03; ES = 0.12) and 1-RMDL (p = 0.04; ES = 0.21) improvements from T0-T2 for FED. Additionally, significant group-by-time interactions were observed for the chronic effects on cortisol (p = 0.03; ES = 0.27) and testosterone levels (p = 0.01; ES = 0.32). Post-hoc tests indicated significant increases of cortisol levels among FAST at T1 and T2 compared to T0 (p = 0.05; ES = 0.41, p = 0.03; ES = 0.34) and a significant increase in cortisol levels in FED at T1 (p = 0.05; ES = 0.29) and T2 (p = 0.04; ES = 0.25). However, the observed increase was lower compared to FAST. Post-hoc tests also indicated significant increases of testosterone only among FED at T2 (p = 0.04; ES = 0.31). A significant group-by-time interaction was found for the acute effect of exercise on cortisol level (p = 0.04; ES = 0.34). The cortisol level immediately after RT was higher in FAST only at T1 (p = 0.03; ES = 0.39) and T2 (p = 0.05; ES = 0.22) compared with T0. No significant group-by-time interactions were identified for sleep quality (p = 0.07; ES = 0.43). Conclusion Muslims can safely practice RT during RF. However, training in a fed state during Ramadan might be more effective than during fasted state for the enhancement of maximal strength with better hormonal responses observed.